2015
DOI: 10.1007/s11356-015-5344-3
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulphate conversion in a methane and acetate fed membrane bioreactor

Abstract: The use of methane and acetate as electron donors for biological reduction of thiosulphate in a 5-L laboratory membrane bioreactor was studied and compared to disproportionation of thiosulphate as competing biological reaction. The reactor was operated for 454 days in semi-batch mode; 30 % of its liquid phase was removed and periodically replenished (days 77, 119, 166, 258, 312 and 385). Although the reactor was operated under conditions favourable to promote thiosulphate reduction coupled to methane oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(53 reference statements)
1
2
2
Order By: Relevance
“…Disproportionation of S2O3 2to SO4 2and H2S has been reported in previous studies Suarez-Zuluaga et al, 2016). In this study, a maximum of 150 mg/L SO4 2was observed after 0.5 to 1 d of S2O3 2addition, clearly indicating the occurrence of microbial disproportionation in the BTF.…”
Section: Disproportionation Of Thiosulphate (S 2 O 3 2-)supporting
confidence: 84%
“…Disproportionation of S2O3 2to SO4 2and H2S has been reported in previous studies Suarez-Zuluaga et al, 2016). In this study, a maximum of 150 mg/L SO4 2was observed after 0.5 to 1 d of S2O3 2addition, clearly indicating the occurrence of microbial disproportionation in the BTF.…”
Section: Disproportionation Of Thiosulphate (S 2 O 3 2-)supporting
confidence: 84%
“…The ANME-3 cells present in the marine Lake Grevelingen possess high specific AOM-SR rates and thus, can be of great potential to be applied in the industry after enrichment. The SR rate with CH 4 as electron donor should be around 100 mmol g VSS -1 d -1 to be competitive with the SR rates achieved with other electron donors, such as hydrogen or ethanol (31, 33), which is still much higher than what was obtained in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…Marine Lake Grevelingen sediment is easily accessible and the ANME-3 cells present possess high specific AOM-SR rates, thus, the use of this sediment as inoculum can be of great potential for the desulfurization of wastewater. However, the SR rate with CH 4 as electron donor should be around 100 mmol gvss −1 d −1 to be competitive with the SR rates achieved with other electron donors, such as hydrogen or ethanol (Meulepas et al, 2009a;Suarez-Zuluaga et al, 2016), which is still much higher than what was obtained in this study. Thus, further enrichment and research is required for potential biotechnological applications of ANME.…”
Section: Methanogenesis Vs Aom-srcontrasting
confidence: 65%